Influence of Podocyte Injury on the Development of Class IV Lupus Nephritis - Zago CCFB; Oliveira BDF; Uehara G; da Silva ALC; Rocha LP; Custódio FB; Araújo LS; da Silva CA; Reis MA; Machado JR (International Journal of Nephrology and Renovascular Disease, 2024)
Cyntia Camilo Franco Borges Zago,1 Bruna de Freitas Oliveira,1 Giovanna Uehara,1 Ana Laura Carvalho da Silva,1 Laura Penna Rocha,1 Fabiano Bichuette Custódio,2 Liliane Silvano Araújo,1 Crislaine Aparecida da Silva,1 Marlene Antônia Reis,1 Juliana Reis Machado1 1Kidney Research Center-Department of Pathology, Genetics and Evolution, Federal University of Triângulo Mineiro, Uberaba, Minas Gerais, Brazil; 2Department of Clinical Medicine, Federal University of Triângulo Mineiro, Uberaba, Minas Gerais, BrazilCorrespondence: Juliana Reis Machado, Kidney Research Center – Department of Pathology, Genetics and Evolution, Federal University of Triângulo Mineiro, Uberaba, Minas Gerais, Brazil, Tel +55 (34) 3700-6450, Email juliana.patologiageral@gmail.comPurpose: In the kidneys, Systemic Lupus Erythematosus leads to Lupus Nephritis (LN), a form of glomerulonephritis. There is evidence that patients with LN may present activation of specific pathways for podocyte injury. This injury can occur through different mechanisms such as loss of podocyte adhesion to the glomerular basement membrane, cell death or dedifferentiation. Podocyturia with consequent podocytopenia has been described in some nephropathies such as LN, highlighting the importance of studying podocyte injuries in this condition. Evaluating in situ morphological characteristics of podocytes becomes relevant for a better understanding of the processes involved in their pathogenesis. This study investigated podocytes in different classes of LN in renal biopsies performed by the Kidney Research Center at the Federal University of Triângulo Mineiro.Patients and Methods: Twenty control cases and 29 biopsy cases diagnosed with LN were selected, divided according to the histopathological classes of the disease. Podocyte density was assessed through immunohistochemistry for Wilms tumor 1 protein and the evaluation of foot process effacement was performed by transmission electron microscopy.Results: Podocyte density was lower in the LN and this reduction was observed in all analyzed classes when compared to the control group. More foot process effacement was observed in the LN group, with more effacement in classes I/II and class IV compared to the control group. The class IV group showed more foot process effacement than the class III group and presented higher proteinuria levels compared to the classes I/II group. A strong, positive, and significant correlation was observed between the activity index and foot process effacement in the class IV group.Conclusion: Podocytes play an important role in the development of LN, and possibly, injuries to these cells are more closely related to the inflammatory/diffuse proliferative cellular process developed in class IV LN.Keywords: podocyte density, foot processes effacement, activity index, renal biopsy